(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the outcome, complications and frequency of re-operation of BPH in Transvesical Prostatectomy and TURP, a ten years single centre study. Study Design: A retrospective comparative study. Place and Duration of Study: This Study was conducted at the Department of Surgery and Allied, SOM Fauji Foundation Hospital, Karachi, Pakistan from January 2001 to May 2010. Materials and Methods: All cases which underwent Open Transvesical Prostatectomy or TURP from January 2001 to May 2010 were reviewed. Total of 360 cases were included, out of which 250 were done by open method and 110 by TURP. Outcome, complications and frequency of re-operation of both the techniques were noted. Data entered into SPSS v.15 and analyzed statistically. Results: Age ranged from 48 to 77 years with a mean age of 57 + 6 years. Hospital stay and catheter removal times were longer in open surgery. Symptom score improvement of 6 points noted in TURP group while 10 points in open surgery group. Four point five percent cases of TURP while 2.8% cases of open surgery needed transfusion. TUR Syndrome was seen in 1.8% of TURP, while no case of open surgery. Stricture urethra developed in 3.6% cases of TURP, while in 0.4% case of open surgery. Urinary Incontinence was seen in 2.7% cases of TURP while nil in open surgery. Re-operation to relieve obstruction needed in 11.8% cases of TURP, while only 1.2% cases of open surgery needed re-operation. Conclusions: There is no statistically significant difference in complications between TURP and open surgery methods, whereas outcome of operation in terms of symptom score improvement was better in open surgery group and no need of re-operation. Disadvantages of open surgery include longer hospital stay and catheter removal time and a scar.